2011
DOI: 10.1002/bmc.1636
|View full text |Cite
|
Sign up to set email alerts
|

On‐line solid‐phase extraction LC‐MS/MS for the determination of Ac‐SDKP peptide in human plasma from hemodialysis patients

Abstract: We developed a high-throughput method based on on-line solid-phase extraction liquid chromatography tandem mass spectrometry (SPE-LC-MS/MS) to determine N-terminal thymosin-β fragment peptide (N-acetyl-seryl-aspartyl-lysyl-proline, Ac-SDKP) in human plasma samples. Quantification of Ac-SDKP was performed using direct injection for on-line SPE based on C(18), reversed-phase LC separation and stable isotope dilution electrospray ionization-MS/MS in multiple reaction-monitoring (MRM) mode. The Ac-SDKP-(13)C(6), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Recent studies have demonstrated the ability of C18 analytical columns to retain the endogenous AcSDKP peptide. [27,28] Thus, the chromatographic behavior of AcSDKP-NH 2 was first evaluated on classic reversed-phase columns such as the Zorbax Stable Bond C18 (Agilent Technology, Les Ulis, France) or the Polaris C18-A (Varian, Palo Alto, USA). In contrast with the behavior of endogenous AcSDKP, [27,28] poor retention of the amidated peptide was observed (data not shown).…”
Section: Hplc Methods Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the ability of C18 analytical columns to retain the endogenous AcSDKP peptide. [27,28] Thus, the chromatographic behavior of AcSDKP-NH 2 was first evaluated on classic reversed-phase columns such as the Zorbax Stable Bond C18 (Agilent Technology, Les Ulis, France) or the Polaris C18-A (Varian, Palo Alto, USA). In contrast with the behavior of endogenous AcSDKP, [27,28] poor retention of the amidated peptide was observed (data not shown).…”
Section: Hplc Methods Optimizationmentioning
confidence: 99%
“…[27,28] Thus, the chromatographic behavior of AcSDKP-NH 2 was first evaluated on classic reversed-phase columns such as the Zorbax Stable Bond C18 (Agilent Technology, Les Ulis, France) or the Polaris C18-A (Varian, Palo Alto, USA). In contrast with the behavior of endogenous AcSDKP, [27,28] poor retention of the amidated peptide was observed (data not shown). This discrepancy could be caused by the increased hydrophilicity of AcSDKP-NH 2 which can be explained by the positive charge afforded by the C-terminal amidation under acidic conditions.…”
Section: Hplc Methods Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it should be a powerful method for preclinical and clinical PK study of puerarin and other isoflavonoids drugs. Currently, the on-line SPE–LC–MS technique has been widely used in analysis of complex biological matrices, such as plasma 11 , 12 , serum 13 and tissue homogenates 14 , etc.…”
Section: New Technology Of On-line Biological Sample Processingmentioning
confidence: 99%
“…Given the potential clinical applications of the peptide, a reliable analytical method is required to facilitate the formulation of the peptide, as well as assess the associated in vivo profile. Although a limited number of quantitative assays for the peptide or its analogue have been reported, these techniques either involved enzyme immunoassays (EIA) [11,12] or liquid chromatography-tandem mass spectrometry (LC-MS/MS) [13][14][15][16]. Pradelles et al first described an EIA for Ac-SDKP in 1990, using acetylcholinesterase-Ac-SDKP conjugate as the tracer, rabbit antiserum, and mouse anti-rabbit IgG antibody-coated 96-well plate.…”
Section: Introductionmentioning
confidence: 99%